Fertilização fosfatada na implantação de Khaya senegalensis A. Juss. - De Vasconcelos, Rodrigo Tenório [UNESP]; Valeri, Sérgio Valiengo [UNESP]; Da Cruz, Mara Cristina Pessôa [UNESP]; Barbosa, José Carlos [UNESP]; De Mattos Barretto, Vitor Corrêa [UNESP] (My University, 2017)
Fertilization in the implantation of African mahogany commercial forests can promote greater initial plant growth and ensure rapid establishment of the stand. However, the commercial plantations with the species are recent and little research on fertilization under field conditions were carried out in Brazil. The objective of this work was to verify the effects of the application of phosphorus doses on growth, macronutrient concentration in leaves, stomatal conductance, transpiration, and photosynthesis and water use efficiency in plants of Khaya senegalensis in the implantation. At the planting, 0, 30, 60, 90 and 120 kg ha-1 of P2O5 were applied in red yellow ultisol and the seedlings were planted at 3 x 2 m spacing in January 2014. The experimental design was randomized blocks with five replications. Height and stem diameter were evaluated at 6, 12, 18 and 24 months after planting. At 12 months the concentration of macronutrients in leaves, stomatal conductance, transpiration, photosynthesis and water use efficiency were determined. Phosphate fertilization promoted greater growth of the plants in the period of one to two years of age, promoting a linear increase in height and diameter at breast height with the increase of phosphorus doses to the maximum dose of 120 kg ha-1 P2O5.
Phosphurus fertilization in Khaya senegalensis A. Juss. implantation
Keywords: African mahogany; Forest fertilization; Nutrition; Ultisol